Auditor’s ethical judgements: assessing the effect of ethical sensitivity and ethical climate / Aida Hazlin Ismail … [et al.] - Ismail, Aida Hazlin; Mohd Sanusi, Zuraidah; Mohd Iskandar, Takiah; Abdul Shukor, Zaleha (Universiti Teknologi MARA Cawangan Selangor, 2016)
This study examined effects of ethical sensitivity and ethical climate on auditors’ ethical judgements. The study employed a ‘between subjects’ experimental design to assess auditors’ judgements on ethical dilemmas relating to issues of independence and confidentiality. Participants consist of 146 auditors from Big 4 and Non Big 4 firms. Results showed ethical sensitivity had a significant positive effect on auditors’ ethical judgements. However, the effect of ethical sensitivity on auditors’ ethical judgements was moderated by the ethical climate of the firm. The positive effect of ethical sensitivity is stronger in higher ethical climate.